A fire-resistant cable and a method for preparing the same

By using polyethylene and ethylene-octene copolymer composite and aluminum hydroxide in the refractory cable, and combining low-temperature cosolvents to form a hard ceramic protective layer, the problem of melting droplets in the refractory cable is solved and the flame retardant and mechanical properties of the refractory layer are improved.

CN116554579BActive Publication Date: 2025-03-07HONGLIANG CABLE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310586650.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-03-07
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

When ceramic polymer materials in refractory cables are formed into porcelain at low temperatures, a large amount of porcelain filler needs to be added, resulting in polyolefin droplet problems.

Method used

Polyethylene and ethylene-octene copolymer are used as the matrix, aluminum hydroxide is used as porcelain powder, and a refractory layer is made with low-temperature cosolvent and calcium carbonate. Polyethylene is toughened by the ethylene-octene copolymer in the blend. Aluminum hydroxide forms a ceramic-shaped shell at high temperature, and the low-temperature cosolvent reduces the porcelain-forming temperature to form a hard ceramic-forming protective layer.

Benefits of technology

The tensile strength and flame retardant properties of the refractory layer are improved, the droplet problem is solved, ensuring that the cable keeps the line open during fire and improving fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of cable manufacturing technology, and specifically discloses a fire-resistant cable and its preparation method. A fire-resistant cable comprises a conductor, an insulating layer, and a fire-resistant layer, wherein the fire-resistant layer comprises the following raw materials in parts by weight: 150-250 parts of polyethylene, 50-100 parts of ethylene-octene copolymer, 10-20 parts of compatibilizer, 10-15 parts of calcium carbonate, 30-40 parts of aluminum hydroxide, 25-30 parts of low-temperature cosolvent, and 5-10 parts of lubricant; its preparation method is as follows: S1. Mix the raw materials of the fire-resistant layer, mix, extrude and granulate to obtain the fire-resistant layer material: S2. Coat the insulating layer and the fire-resistant layer material on the surface of the conductor successively, cool and solidify, and cut to obtain a fire-resistant cable. The tensile strength of the fire-resistant layer of the cable in the present application can reach 33.5-35.5MPa, the limiting oxygen index can reach 31.5-33.8%, and there is no droplet after burning for 90s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cable manufacturing, and more specifically, to a fire-resistant cable and a preparation method thereof. Background Art

[0002] Fire-resistant cables refer to cables that can operate normally for a certain period of time in the event of a cable fire while the external flame is still burning, maintaining the integrity of the wire and cable lines and the normal operation of the line equipment. Fire-resistant cables are widely used in high-rise buildings, subways, underground streets, large power stations, and important industrial and mining enterprises, and other places related to fire safety and firefighting and lifesaving.

[0003] Ceramic polymer material is a commonly used refractory material in fire-resistant cables. Ceramic polymer refractory material is a special polymer refractory material with a polymer as the base material, generally a polyolefin as the base material, with ceramic additives and functional fillers added, and a certain processing procedure. Ceramic polyolefin used for fire-resistant cables has excellent fireproofing, fire resistance, flame retardancy, low smoke, non-toxicity and other properties. When a fire occurs in a ceramic polyolefin cable, the inorganic filler quickly forms a ceramic shell when burning at high temperature, which becomes a fire-resistant protective layer covering the cable core, which can ensure that the cable line remains unobstructed for a certain period of time after the fire occurs.

[0004] In view of the above-mentioned related technologies, the applicant believes that polyolefin ceramic polymer materials can achieve low-temperature ceramicization, but the amount of ceramic filler required is large, which will cause polyolefin droplet problems. Summary of the invention

[0005] In order to solve the molten drop problem of fire-resistant cables, the present application provides a fire-resistant cable and a preparation method thereof.

[0006] In a first aspect, the present application provides a fire-resistant cable, which adopts the following technical solution:

[0007] A fire-resistant cable comprises a conductor, an insulating layer and a fire-resistant layer. The fire-resistant layer comprises the following raw materials in parts by weight: 150-250 parts of polyethylene, 50-100 parts of ethylene-octene copolymer, 10-20 parts of a compatibilizer, 10-15 parts of calcium carbonate, 30-40 parts of aluminum hydroxide, 25-30 parts of a low-temperature co-solvent and 5-10 parts of a lubricant.

[0008] By adopting the above technical scheme, the brittle disadvantage of polyethylene can be greatly improved by using polyethylene and ethylene-octene copolymer as the matrix. In the blend, ethylene-octene copolymer plays a toughening role on polyethylene, which improves the tensile strength and tensile strain at break of the material. Aluminum hydroxide is used as a porcelain powder. Aluminum hydroxide is decomposed under high temperature conditions to release crystal water. The released crystal water is not only a coolant but also a diluent, absorbing a large amount of heat. At the same time, the aluminum oxide produced by the dehydration decomposition reaction has a very high specific surface area, which will form a ceramic shell covering the material to isolate the combustible gas, further playing a flame retardant effect. The ceramic shell formed by combustion does not melt or fall off the cable during high-temperature combustion. The ceramic shell formed by aluminum hydroxide during the combustion process is a honeycomb ceramic shell with fine pores, which has a good effect of fire insulation, heat insulation, and isolation of combustible gas. The low-temperature co-solvent can effectively reduce the porcelain-forming temperature of the porcelain powder. The low-temperature co-solvent combined with calcium carbonate can obtain the required ceramic shell strength in a wider temperature range and expand its temperature response range.

[0009] Preferably, the preparation method of the low-temperature co-solvent is:

[0010] The boron oxide and zinc oxide powders are mixed and ball-milled, and then sintered once, the sintering temperature is 600-650°C, the sintering time is 2-3h, the powder is ball-milled again after the first sintering, and then sintered twice, the sintering temperature is 800-850°C, the sintering time is 2-3h, and a low-temperature solvent is obtained.

[0011] By adopting the above technical scheme, boron oxide and zinc oxide are used to prepare ceramic zinc borate low-temperature flux. The synthesized flux can melt when the ablation temperature reaches 700°C or above to form a liquid phase with good crystallinity, which is helpful for the ceramic filler to form a ceramic layer. When polyethylene is exposed to an open flame or high temperature environment, it is first decomposed by heat. As the temperature rises, under the action of surface energy, the particles are rearranged, and the synthesized low-temperature flux melts to form a liquid phase, which penetrates into the aluminum hydroxide, calcium carbonate and the residues of polyethylene decomposition to form a low eutectic, which can play a bridging role for other inorganic particles. As the temperature continues to rise, a hard and dense ceramic protective layer is finally formed.

[0012] In addition, at high temperatures, aluminum hydroxide decomposes to generate crystal water, which reduces the system temperature and improves flame retardancy. The low-temperature co-solvent and the aluminum hydroxide system have a synergistic effect, which can not only reduce the system temperature but also promote the formation of a surface coke layer, thereby achieving a better flame retardant effect.

[0013] Preferably, the weight ratio of boron oxide to zinc oxide is (2-3):1.

[0014] Preferably, the weight ratio of boron oxide to zinc oxide is 2.7:1.

[0015] By adopting the above technical solution, the ratio of boron oxide to zinc oxide is adjusted to achieve a better vitrification effect, improve the flame retardancy of the refractory layer, and solve the molten drop problem.

[0016] Preferably, the aluminum hydroxide is surface treated with a silane coupling agent.

[0017] By adopting the above technical scheme, aluminum hydroxide is surface treated with a silane coupling agent, and the surface of aluminum hydroxide is converted from an inorganic surface to an organic surface, thereby increasing the compatibility of aluminum hydroxide with polyethylene and ethylene-octene copolymer, reducing defects and stress concentration points in the sample, and improving the tensile strength and elongation at break of the refractory layer material, thereby improving its fire resistance to a certain extent.

[0018] Preferably, the weight ratio of the polyethylene to the ethylene-octene copolymer is: (2-3):1.

[0019] By adopting the above technical solution, the ratio of polyethylene to ethylene-octene copolymer is adjusted, so that the flexibility and elasticity of ethylene-octene copolymer are combined with the high temperature resistance, electrical insulation and impact resistance of polyethylene, thereby improving the comprehensive performance of the synthetic material.

[0020] Preferably, the compatibilizer is a maleic anhydride grafted polyolefin compatibilizer.

[0021] By adopting the above technical solution, maleic anhydride contains carbon-carbon double bonds and some active hydrogen molecules, so maleic anhydride has strong graft polymerization ability and high grafting efficiency. Using maleic anhydride grafted polyolefin as a compatibilizer can improve the comprehensive performance of the material, reduce the amount of base resin, improve the cost performance, and improve the disadvantage of difficult processing of the mixture.

[0022] Preferably, the lubricant is zinc stearate and polyethylene wax in a weight ratio of (1-2):1.

[0023] A large amount of ceramic powder is added to ceramic polyolefin. During the processing, the viscosity of ceramic polyolefin is very high, and friction will occur between ceramic polyolefins, which is not good for melt fluidity. By adopting the above technical solution, zinc stearate and polyethylene wax are compounded as lubricants to improve the fluidity of the mixture, reduce the friction between materials and between materials and equipment, and zinc stearate and polyethylene wax are conducive to the mixing of ceramic polyolefins, and the insulation resistance is higher at high temperatures; in addition, zinc stearate and polyethylene wax can not only improve the smoothness of the material surface, but also improve the lubrication effect of the polymer system, making the ceramic polyolefin more uniform.

[0024] Preferably, 8-12 parts of red phosphorus are also included.

[0025] By adopting the above technical solution, during high-temperature sintering, the red phosphorus in the system promotes the formation of quartz crystals and improves the self-supporting ability of the material; as the ablation temperature increases, the internal pores of the ceramic body decrease and the bending strength increases.

[0026] In a second aspect, the present application provides a method for preparing a fire-resistant cable, using the following technical solution:

[0027] A method for preparing a fire-resistant cable comprises the following steps:

[0028] S1. Mixing, mixing and extruding the refractory raw materials to obtain the refractory material:

[0029] S2. The insulating layer and the refractory layer are coated on the surface of the conductor in sequence, and the conductor is cut after being cooled and solidified to obtain a refractory cable.

[0030] By adopting the above technical solution, the preparation method of the present application is simple and easy to operate, has no special requirements for production equipment, and is suitable for industrial production.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. Since the present application adopts a composite of polyethylene and ethylene-octene copolymer as the matrix, aluminum hydroxide as the porcelain powder, and a low-temperature co-solvent and calcium carbonate to make a refractory layer, the obtained refractory layer has a tensile strength of 33.5-35.5MPa and a limiting oxygen index of 31.5-33.8%, and there is no droplet after burning for 90s.

[0033] 2. In the present application, boron oxide and zinc oxide are preferably used to prepare ceramic zinc borate low-temperature solvent to further improve the flame retardancy and fire resistance of the refractory layer. DETAILED DESCRIPTION

[0034] The present application is further described in detail below with reference to the embodiments.

[0035] Preparation examples of raw materials and intermediates

[0036] raw material

[0037] Polyethylene, low-density polyethylene, injection molding grade;

[0038] Ethylene-octene copolymer, Dow 8150;

[0039] Compatibilizer, maleic anhydride grafted polyolefin, Arkema PP CA100;

[0040] Lubricant, zinc stearate; Polyethylene wax, Acmec S77400;

[0041] Silane coupling agent, vinyltrimethoxysilane.

[0042] Preparation Example

[0043] Preparation Example 1

[0044] A low-temperature co-solvent, the preparation method of which is as follows:

[0045] 2kg of boron oxide and 1kg of zinc oxide powder are put into a ball mill and mixed and ball-milled at a speed of 300r / min for 30min, and then sintered once, the sintering temperature is 600℃, and the sintering time is 3h. After the first sintering, the powder is put into the ball mill again and ball-milled at a speed of 280r / min for 30min, and then sintered twice, the sintering temperature is 800℃, and the sintering time is 3h to obtain a low-temperature solvent.

[0046] Preparation Example 2

[0047] A low-temperature co-solvent, the preparation method of which is as follows:

[0048] Different from Preparation Example 1, the amount of boron oxide used in Preparation Example 2 is 2.7 kg.

[0049] Preparation Example 3

[0050] A low-temperature co-solvent, the preparation method of which is as follows:

[0051] Different from Preparation Example 1, the amount of boron oxide used in Preparation Example 3 is 3 kg.

[0052] Preparation Example 4

[0053] A low-temperature co-solvent, the preparation method of which is as follows:

[0054] Different from Preparation Example 1, the amount of boron oxide used in Preparation Example 4 is 1.5 kg.

[0055] Preparation Example 5

[0056] A low-temperature co-solvent, the preparation method of which is as follows:

[0057] Different from Preparation Example 1, the amount of boron oxide used in Preparation Example 5 is 3.5 kg.

[0058] Preparation Example 6

[0059] A modified aluminum hydroxide, the preparation method of which is:

[0060] The aluminum hydroxide was immersed in the silane coupling agent vinyltrimethoxysilane for 15 minutes, then taken out and dried at 80°C to obtain modified aluminum hydroxide. Example

[0061] Examples 1-5

[0062] A fire-resistant cable, the preparation method of which is as follows:

[0063] S1. Conductor preparation

[0064] The copper rod is drawn by a wire drawing machine to be drawn into a 2.5 mm copper single wire. The drawn copper single wire is automatically annealed in an environment with an air pressure of 2.5 MPa. The coefficient voltage of the automatic annealing is 24.5 V, the coefficient current is 900 A, and the line speed is 150 m / min. After the annealing is completed, a conductor single wire is obtained. Then, 5 strands of conductor single wires are rewound on a rewinding machine for a corresponding number, and after being twisted by a tube twisting machine, a conductor of the cable is formed.

[0065] S2. Insulation wrap:

[0066] Wrap the conductor obtained in S1 with a polyvinyl chloride insulation layer;

[0067] S3. Refractory wrap

[0068] According to the raw material ratio in Table 1, polyethylene, ethylene-octene copolymer, compatibilizer and lubricant were added into the mixer, heated to 80°C, and reacted for 1.2h to obtain a premix;

[0069] Adding calcium carbonate, aluminum hydroxide and low-temperature co-solvent into the premix and kneading at a temperature of 120° C. to obtain a mixture;

[0070] The mixed material is extruded and granulated using a parallel twin-screw extruder to obtain a refractory layer material;

[0071] The fire-resistant layer material is coated on the outside of the insulation layer of S2, and after cooling and solidification, it is cut to obtain a fire-resistant cable.

[0072] Example 1-5 Raw material ratio table (kg)

[0073]

[0074] Wherein, the compatibilizer is a maleic anhydride grafted polyolefin compatibilizer; the lubricant is zinc stearate and polyethylene wax in a weight ratio of 1:1; and the low-temperature cosolvent comes from Preparation Example 1.

[0075] Example 6

[0076] Different from Example 2, the lubricant in Example 6 is zinc stearate and polyethylene wax in a weight ratio of 2:1.

[0077] Example 7

[0078] Different from Example 2, the lubricant in Example 7 is zinc stearate.

[0079] Example 8

[0080] The difference from Example 2 is that the low-temperature co-solvent in Example 8 comes from Preparation Example 2.

[0081] Example 9

[0082] Different from Example 2, the low-temperature co-solvent in Example 9 comes from Preparation Example 3.

[0083] Example 10

[0084] Different from Example 2, the low-temperature co-solvent in Example 10 comes from Preparation Example 4.

[0085] Embodiment 11

[0086] Different from Example 2, the low-temperature co-solvent in Example 11 comes from Preparation Example 5.

[0087] Example 12

[0088] Different from Example 8, in Example 12, an equal amount of modified aluminum hydroxide from Preparation Example 6 is used to replace aluminum hydroxide.

[0089] Embodiment 13

[0090] The difference from Example 12 is that the raw materials in Example 12 also include 8 kg of red phosphorus, and the preparation method is as follows:

[0091] S1. Conductor preparation

[0092] Same as Example 12;

[0093] S2. Insulation wrap:

[0094] Same as Example 12;

[0095] S3. Refractory wrap

[0096] According to the raw material ratio in Table 1, polyethylene, ethylene-octene copolymer, compatibilizer and lubricant were added into the mixer, heated to 80°C, and reacted for 1.2h to obtain a premix;

[0097] Adding calcium carbonate, aluminum hydroxide, low-temperature co-solvent and red phosphorus into the premix and kneading at a temperature of 120° C. to obtain a mixture;

[0098] The mixed material is extruded and granulated using a parallel twin-screw extruder to obtain a refractory layer material;

[0099] The fire-resistant layer material is coated on the outside of the insulation layer of S2, and after cooling and solidification, it is cut to obtain a fire-resistant cable.

[0100] Examples 14-15

[0101] Different from Example 13, the amounts of red phosphorus used in Examples 14-15 are 12 kg and 15 kg respectively.

[0102] Comparative Example

[0103] Comparative Example 1

[0104] The difference from Example 1 is that in Comparative Example 1, an equal amount of low-temperature co-solvent is used to replace calcium carbonate.

[0105] Comparative Example 2

[0106] Different from Example 1, in Comparative Example 2, an equal amount of polyethylene was used to replace the ethylene-octene copolymer.

[0107] Comparative Example 3

[0108] Different from Example 1, in Comparative Example 3, an equal amount of kaolin was used to replace aluminum hydroxide.

[0109] Comparative Example 4

[0110] Different from Example 1, the low-temperature co-solvent in Comparative Example 4 is zinc borate.

[0111] Performance testing

[0112] Detection method / test method

[0113] The following performance tests were performed on the refractory layer material obtained in step S3 in the embodiment and the comparative example. The performance test results are shown in Table 2:

[0114] Tensile strength determination: Conduct a tensile test according to the method in "Determination of tensile properties of plastics" GB / T1040-2018 to determine the tensile strength;

[0115] Limiting oxygen index determination: Determine the limiting oxygen index according to the method in "Determination of combustion behavior of plastics by oxygen index method" GB / T 2406.1-2008;

[0116] Determination of the number of molten droplets: Ignite the sample and measure the number of molten droplets within 90 seconds of combustion.

[0117] Table 2 Performance test results

[0118]

[0119] Combining Examples 1-15 and Comparative Examples 1-4 and Table 2, it can be seen that the tensile strength and limiting oxygen index in Examples 1-16 are higher than those in Comparative Examples 1-4, and the number of droplets within 90 seconds is lower than that in Comparative Examples 1-4, which shows that the refractory layer of the present application has excellent mechanical properties and flame retardant properties, no droplet problem, excellent comprehensive performance, and high economic value.

[0120] Combining Example 1 with Comparative Example 1 and Table 2, it can be seen that if Comparative Example 1 does not contain calcium carbonate, the limiting oxygen index in Comparative Example 1 is reduced, and there will be a droplet phenomenon, which shows that the addition of calcium carbonate can improve the flame retardant and fire resistant properties of the refractory layer; this may be because calcium carbonate can be compounded with a low melting point solvent, melt during combustion, and fully bond the porcelain-forming filler and the residues of the polyethylene matrix decomposition together to form a liquid bridge-like skeleton, forming crystals, and will not cause droplet problems.

[0121] Combining Example 1 with Comparative Example 2 and Table 2, it can be seen that the matrix in Comparative Example 2 is only polyethylene, then the limiting oxygen index in Comparative Example 2 is reduced, and the tensile strength is significantly reduced, which shows that the use of polyethylene and ethylene-octene copolymer as a matrix can not only improve the flame retardant properties of the fire-resistant layer, but also improve its mechanical properties; this may be because the ethylene-octene copolymer in the blend has a toughening effect on the polyethylene, thereby increasing the tensile strength and tensile strain at break of the material.

[0122] Combining Example 1 with Comparative Example 3 and Table 2, it can be seen that aluminum hydroxide is used as a porcelain-forming material in Example 1, and kaolin is used as a porcelain-forming material in Comparative Example 3. Compared with Example 1, the limiting oxygen index in Comparative Example 3 is significantly reduced, and a molten drop phenomenon occurs, which indicates that the use of aluminum hydroxide as a porcelain-forming material can be combined with a matrix and a co-solvent to improve the flame retardant properties of the refractory layer without causing a molten drop problem; this may be because the low-temperature co-solvent can effectively reduce the porcelain-forming temperature of the porcelain powder, and the low-temperature co-solvent can be combined with calcium carbonate to obtain the required ceramic shell strength within a wider temperature range, thereby expanding its temperature response range. Aluminum hydroxide is decomposed by heat under high temperature conditions to release crystal water, and the released crystal water is not only a coolant but also a diluent, absorbing a large amount of heat; at the same time, the aluminum oxide produced by the dehydration decomposition reaction has a very high specific surface area, and will form a ceramic shell covering the material to isolate the combustible gas, further playing a flame retardant effect, and the ceramic shell formed by combustion does not melt or fall off the cable during high-temperature combustion.

[0123] Combining Example 1 with Comparative Example 4 and Table 2, it can be seen that an obvious melting drop phenomenon occurs in Comparative Example 4, which indicates that the low-temperature solvent of the present application can effectively solve the melting drop problem; this may be because boron oxide and zinc oxide are used to prepare ceramic zinc borate low-temperature solvent, and the synthesized solvent can melt when the ablation temperature reaches 700°C or above to form a liquid phase with good crystallinity; when polyethylene is decomposed by heat, the synthesized low-temperature flux melts to form a liquid phase, penetrates between aluminum hydroxide, calcium carbonate and the residues of polyethylene decomposition, and forms a eutectic, which can play a bridging role for other inorganic particles. As the temperature continues to rise, a hard and dense ceramic protective layer is eventually formed, which will not cause the melting drop problem.

[0124] Combining Example 2 with Examples 8-10 and Table 2, it can be seen that the ratio of boron oxide to zinc oxide in the synthesis of low-temperature solvents will affect the limiting oxygen index of the refractory layer, and the ratio in Example 8, that is, Preparation Example 2, is better.

[0125] Combining Example 12 with Examples 13-15 and Table 2, it can be seen that red phosphorus is added to Examples 13-15, and the limiting oxygen index of the refractory layer in Examples 13-15 is improved compared with Example 12, which shows that the addition of red phosphorus can improve the flame retardant properties of the material. This may be because during warm sintering, the red phosphorus in the system promotes the formation of quartz crystals and improves the self-supporting ability of the material; as the ablation temperature increases, the internal pores of the ceramic body are reduced and the flame retardant properties are improved.

[0126] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A fire-resistant cable, comprising a conductor, an insulating layer, and a fire-resistant layer, characterized in that: The fire-resistant layer comprises the following raw materials in parts by weight: 150-250 parts of polyethylene, 50-100 parts of ethylene-octene copolymer, 10-20 parts of compatibilizer, 10-15 parts of calcium carbonate, 30-40 parts of aluminum hydroxide, 25-30 parts of low-temperature co-solvent, and 5-10 parts of lubricant; the weight ratio of the polyethylene to the ethylene-octene copolymer is: (2-3): 1; The preparation method of the low-temperature solvent comprises: mixing boron oxide and zinc oxide powder, ball-milling, and then sintering once, wherein the sintering temperature is 600-650° C., and the sintering time is 2-3 hours; after the first sintering, the powder is ball-milled again, and then sintered twice, wherein the sintering temperature is 800-850° C., and the sintering time is 2-3 hours, to obtain the low-temperature solvent; The weight ratio of the boron oxide to the zinc oxide is (2-3):

1.

2. A fire-resistant cable according to claim 1, characterized in that: The weight ratio of the boron oxide to the zinc oxide is 2.7:

1.

3. A fire-resistant cable according to claim 1, characterized in that: The aluminum hydroxide is surface treated with a silane coupling agent.

4. A fire-resistant cable according to claim 1, characterized in that: The compatibilizer is a maleic anhydride grafted polyolefin compatibilizer.

5. A fire-resistant cable according to claim 1, characterized in that: The lubricant is zinc stearate and polyethylene wax in a weight ratio of (1-2):

1.

6. A fire-resistant cable according to claim 1, characterized in that: Also included is 8-12 parts by weight of red phosphorus.

7. A method for preparing a fire-resistant cable according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Mixing, mixing and extruding the refractory raw materials to obtain the refractory material: S2. The insulating layer and the refractory layer are coated on the surface of the conductor in sequence, and the conductor is cut after being cooled and solidified to obtain a refractory cable.

Citation Information

Patent Citations

  • Ceramic flame-retardant and fire-resistantsilicone rubbercompositematerial and preparation method thereof

    CN106832960A

  • Fireproof flame-retardant cable and preparation method thereof

    CN112391014A

  • Ceramic polyolefin refractory material with low combustion heat value and preparation method thereof

    CN113213953A